Study of the Artificial Intelligence Role in Achieving Cybersecurity for Critical Information Infrastructure - Agus Kurniati (Monas: Jurnal Inovasi Aparatur, 2024)
This research aims to examine the role of Artificial Intelligence (AI) in strengthening cybersecurity for critical information infrastructure (CII) in Indonesia. The research methodology used is a systematic literature review (SLR) involving identification, review, and evaluation, data collected through literature studies relevant to the research topic. Data were analyzed using critical synthesis method, gap analysis and SOAR (Strengths, Opportunities, Aspirations, Results) analysis, compared with the NIST Cybersecurity Framework to determine suitable strategic alternatives. The research results indicate that AI can strengthen cybersecurity in the CII sector by enhancing threat detection and response capabilities and optimizing risk management. The study also identified potential opportunities, such as cross-sector collaboration and the development of innovative technologies, as well as challenges, including the need to maintain transparency and ethical AI. In addition, the proposed strategy to realize AI as a tool in cyber security includes strengthening investment in technology, increasing human resource skills, and supporting development policies while taking into account potential risks that may arise, such as privacy violations, data leaks, and potential bias in decision making by AI systems. It is hoped that the results of this research will provide insight for stakeholders in efforts to strengthen cyber security in the IIV sector in Indonesia.